Corporate Governance Practices and Financial Distress: Empirical Evidence from Listed Companies in Sri Lanka - S. Balagobei; G. Keerthana (Kelaniya Journal of Management, 2023)
The study aims to investigate the impact of corporate governance on financial distress of listed companies in Sri Lanka. Board size, board composition, CEO duality, board meeting, director ownership, and audit committee size are proxies for corporate governance while financial distress is measured by the Altman Z-score. Altman Z-score measures financial distress inversely and bigger the Z-score indicates the smaller the risk of financial distress. Using hundred and eight individual observations of firms listed in Sri Lanka for the period of 2019 to 2021 and employing fixed effects model, the effect of corporate governance practices on financial distress is evaluated. The results from panel data regression analysis reveal that firms having large number of directors on the board have a low likelihood of financial distress of listed companies in Sri Lanka. Furthermore, when a chief executive officer serves as the chairman of the board at a company, the more likely it is that the company will experience financial distress. But, board composition, audit committee size, board meeting and director ownership have not shown any significant impact on financial distress. The current study also provides evidence that firm-specific characteristics such as firm size, leverage and profitability, could be useful as to determining the likelihood of financial distress. The findings may be of prominence to the academic researchers, practitioners, and regulators who are interested in discovering the quality of corporate governance practices in a developing market and its impact on financial distress.